Depression, anxiety and post-traumatic growth among COVID-19 survivors six-month after discharge. Issue 1 (31st December 2022) - Xiao, Xin; Yang, Xue; Zheng, Weiran; Wang, Bingyi; Fu, Leiwen; Luo, Dan; Hu, Yuqing; Ju, Niu; Xu, Hui; Fang, Yuan; Fong Chan, Paul Shing; Xu, Zhijie; et al.
ABSTRACT: Background: Pre-hospitalisation, hospitalisation and post-hospitalisation factors may significantly affect depression, anxiety and post-traumatic growth (PTG) among COVID-19 survivors. Objective: Our study investigated depression, anxiety and PTG and their correlates among COVID-19 survivors. Method: A cross-sectional telephone survey recruited 199 COVID-19 patients (Mean age = 42.7; 53.3% females) at six-month follow-up after hospital discharge in five Chinese cities (i.e. Wuhan, Shenzhen, Zhuhai, Dongguan and Nanning). Their demographic information, clinical records and experiences during (e.g. severity of covid-19 symptoms, treatment and exposure to other patients' suffering) and after hospitalisation (e.g. perceived impact of covid-19, somatic symptoms after hospitalisation), and psychosocial factors (e.g. perceived discrimination, self-stigma, affiliate stigma, resilience and social support) were investigated. Depressive and anxiety symptoms were measured by the Patient Health Questionnaire (PHQ-9) and the Generalised anxiety disorder (GAD-7) scale, respectively. PTG was examined by the Post-traumatic Growth Inventory (PTGI) instrument. Results: The proportion of depressive symptoms <5, ≥5 and <10, ≥10 were 76.9%, 12.0% and 11.1%, respectively. The proportion of anxiety symptoms <5, ≥5 and <10, ≥10 were 77.4%, 15.1% and 7.5%, respectively. Multivariate logistic regression showed that receiving mental health care services during hospitalisation, somatic symptoms after discharge, perceived affiliate stigma and perceived impact of being infected with COVID-19 were significantly and positively associated with probable depression. Significant correlates of probable anxiety also included permanent residents of the city, somatic symptoms after discharge, perceived impact of being infected with COVID-19 and self-stigma. Social support, self-stigma and receiving mental health care services during hospitalisation were positively associated with PTG. Conclusions: The results suggest that post-hospitalisation and psychosocial factors had relatively stronger associations with depression, anxiety and PTG than pre-hospitalisation and hospitalisation factors. Promoting social support and social inclusion may be useful strategies to improve the mental health of COVID-19 survivors. HIGHLIGHTS: Post-hospitalisation and psychosocial factors had relatively stronger associations with depression, anxiety and PTG than pre-hospitalisation and hospitalisation factors, promoting social support and social inclusion may be useful strategies to improve mental health of COVID-19 survivors.